The high quality structural documentation of social work described by social workers - Hujanen, Kaisa; Kinnunen, Ulla-Mari; Ailio, Erja; Koivumäki, Leena (Finnish Journal of eHealth and eWelfare, 2021)
Conscientious and high quality documentation is an essential part of social work. Social work is about change and development, where results and effectiveness can be proven through careful, high quality documentation. The local and nationwide development of social work and decision making requires coherent and carefully obtained information. High quality documentation is also a requirement for the continuity of social work and client information. Client records created in social work have many different uses, but they are primarily created for clients themselves. The purpose of this study was to describe what kind of views social workers have on high quality structural documentation and their prerequisitions. The material of the study was collected via interviewing social workers (n=6) who are working in adult social work and who document and process structural documentation in their work. As a theoretical frame of reference the study used the nursing reference model, which was modified into the context of social work. The research material was analyzed by using content analysis. According to the study results the prerequisitions of a high quality structural documentation are using standardized documents during case recording, a thorough introduction to documentation, using the documentation practises which are jointly implemented into the working team and providing enough time for case recording. According to the study results, high quality structural documents are timely and up to date and the information which is recorded is essential to the client work. The documents are understandable to the reader when the language used is unambiguous and clear, concise and going logically onward. In the documents the client’s voice is heard and different sources of information are clearly separated from each other. As a conclusion it can be stated that social workers describe the quality of case records primarily from the perspective of client work and client participation.